The Implementation of EMU (English Moslem Union) Approach in Developing Islamic Studies and English Competence of UNTIDAR Moslem Students: (A Case Study Conducted at TIDAR University) - Farikah Farikah (International Islamic Schools Alliance, 2016)
The purpose of this research is to describe the implementation of EMU (English Moslem Union) Approach in developing islamic studies and English competence among the moslem students of Tidar University (UNTIDAR). EMU Approach is a way of developing Islamic studies as well as English competence. Through EMU, the students of UNTIDAR study Islam as well as English with Halaqoh model. Halaqoh is a term used in Islamic education. Halaqoh (circle) is used to describe a group with about 8 or 10 persons who learn islamic studies regularly. One of them is as murrabi (teacher) and the others are as mutarabbi (students). This descriptive qualitative study employed in-depth interviews, and on-site observation in collecting the data. Following Milles and Hubberman’s theory (1994), the writer analyzed the data through data reduction, data display, conclusion and verification. The triangulation was employed in checking the validity of the data. The results show that the implementation of EMU through Halaqoh model is an effective way to develop Islamic studies and English competence of Tidar University students. It can be seen from two indicators. The first, it can be seen from the students’ characters in terms of nature, attitude and habit.The second is from the students’ competence in English through discussion activities.